The Construction of the nurse’s professional identity: a passage through mirrors - Baptista, Beatriz Guitton Renaud (Online Brazilian Journal of Nursing, 2002)
The subject of the thesis is the construction of the nurse’s professional identity with emphasis on the social representations of nurses about three moments, understood as passages through mirror: the periods before the university entrance; during the university studies and after graduation. A qualitative approach was used, Scenes of Aesthetic Production were used as a methodological strategy for data production and the analysis was based on multireferentiality and on social representations. In Passage through the 1st Mirror, “The death of the teenage dream”, the simultaneous construction of the professional identity and the process of adolescent identification, they search for a profession that could fulfill their desire to care but is compatible with the family’s socio-economic condition, are examined. In Passage through the 2nd Mirror, “The Construction of the Resistance Identity”, they search for strategies to break the rigid and dominating teaching model. And in Passage through the 3rd Mirror, “The Construction of the Project Identity”, the students highlighted practical issues of the nurse’s daily routine, such as qualification, autonomy and professional recognition. We came to the conclusion that the construction of the professional identity of the nurse is a dynamic process that is in the process of shifting emphasis to identification with the self, the intersubjectivity of the human action, as a function of social well-being, liberty of expression and the preservation of environmental equilibrium.